2014
DOI: 10.1371/journal.ppat.1004097
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Helper T Cells Promote Liver Pathology in Mice during Schistosoma japonicum Infection

Abstract: Following Schistosoma japonicum (S. japonicum) infection, granulomatous responses are induced by parasite eggs trapped in host organs, particular in the liver, during the acute stage of disease. While excessive liver granulomatous responses can lead to more severe fibrosis and circulatory impairment in chronically infected host. However, the exact mechanism of hepatic granuloma formation has remained obscure. In this study, we for the first time showed that follicular helper T (Tfh) cells are recruited to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 80 publications
(95 reference statements)
2
53
0
Order By: Relevance
“…11,12 In recent studies, it was reported that Th17/IL-17 and follicular helper T cells (Tfh)/IL-21 were correlated with severe pathology and subsequent fibrosis in schistosomiasis. 13,14 Down-regulation of Th17/IL-17 or Tfh/IL-21 could decrease granulomatous inflammation and ameliorate liver fibrosis. [15][16][17] During the chronic phase, the Th2 response is still predominant and modulated, but the granulomas are smaller than at earlier stages. The reason is that regulatory T cells play an important repressor role in the down-regulation of pathological immune responses at this stage.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 In recent studies, it was reported that Th17/IL-17 and follicular helper T cells (Tfh)/IL-21 were correlated with severe pathology and subsequent fibrosis in schistosomiasis. 13,14 Down-regulation of Th17/IL-17 or Tfh/IL-21 could decrease granulomatous inflammation and ameliorate liver fibrosis. [15][16][17] During the chronic phase, the Th2 response is still predominant and modulated, but the granulomas are smaller than at earlier stages. The reason is that regulatory T cells play an important repressor role in the down-regulation of pathological immune responses at this stage.…”
Section: Introductionmentioning
confidence: 99%
“…Are Tfh cells harmful to Trichinella? A previous study reported a role for Tfh cells in a Schistosoma japonicum infection model (29). That study found that when ICOSdeficient mice with impaired Tfh differentiation were infected with S. japonicum, amelioration of liver pathology was observed, and also that the adaptive transfer of Tfh cells into ICOS-deficient mice reestablished the liver pathology with enhanced cell accumulation in granulomas, indicating that Tfh cells are involved in the pathology of helminth infection.…”
Section: Discussionmentioning
confidence: 88%
“…Although our previously published data documents that Tfh cells represent a key pathogenic player in schistosomiasis japonica, little is known about how Tfh cells promote the granuloma formation. Given that the granuloma is characterized by the eosinophil‐rich granulomatous lesions, we wondered whether Tfh cells promote the granuloma formation through recruiting the eosinophils into the liver during schistosome infection.…”
Section: Resultsmentioning
confidence: 95%
“…Given that the granuloma is characterized by the eosinophil‐rich granulomatous lesions, we wondered whether Tfh cells promote the granuloma formation through recruiting the eosinophils into the liver during schistosome infection. In ICOSL knockout (KO) mice, a widely used Tfh cell deficiency model, we showed a distinct reduction in the cellularity of granulomas surrounding single schistosome eggs after S japonicum infection (Figure A). Notably, the relative number of eosinophils in granulomas was substantially reduced in Tfh cell‐deficient mice (Figure B).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation